2009
DOI: 10.4269/ajtmh.2009.08-0344
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Distribution and Prevalence of Schistosomiasis and Soil-Transmitted Helminths among Schoolchildren in Mozambique

Abstract: Schistosomiasis and soil-transmitted helminths (STHs) are most prevalent in developing countries. In Mozambique, the first and only national survey of the distribution and prevalence of schistosomiasis and STHs was conducted in 1952 and 1957. Only occasional surveys in restricted areas have been conducted since the 1950s. The objective of our survey was to update information on the geographic distribution and prevalence of schistosomiasis and STHs in this country. During August 2005–June 2007, the Schistosomia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
76
4
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 6 publications
5
76
4
2
Order By: Relevance
“…Factors such as poor nutritional status, genetic red blood cell disorders or parasitic infections have been suggested to account for low Hb values. While a fairly low frequency of sickle cell trait (5.6%) was reported in an early study of pregnant women in Mozambique [32], a recent national survey of schistosomiasis and soil-transmitted helminthes showed that parasitic infections are common [33].…”
Section: Discussionmentioning
confidence: 90%
“…Factors such as poor nutritional status, genetic red blood cell disorders or parasitic infections have been suggested to account for low Hb values. While a fairly low frequency of sickle cell trait (5.6%) was reported in an early study of pregnant women in Mozambique [32], a recent national survey of schistosomiasis and soil-transmitted helminthes showed that parasitic infections are common [33].…”
Section: Discussionmentioning
confidence: 90%
“…In a previous report, we demonstrated that urinary schistosomiasis, hookworm disease and other intestinal parasitic infections are highly prevalent in Mozambican schoolchildren in most provinces of the country 1 . Our survey aims to assess hookworm infection and urinary schistosomiasis associated anemia in schoolchildren living in three provinces of northern Mozambique.…”
Section: Introductionmentioning
confidence: 86%
“…30,31 Malaria and intestinal helminthes are prevalent, and iron-deficiency anemia is thought to be common. [32][33][34] During Mozambique's initial response to the HIV epidemic, first-level health workers used a 2005 Mozambican guideline adapted from a standard World Health Organization guideline recommending that anemia (or pallor) be treated with presumptive iron supplementation, anthelminthics, and antimalarials. 35 In 2009, the Mozambican Ministry of Health (MISAU) updated its anemia guideline to address several concerns: overprescription of antimalarials, underdetection of treatable HIV-associated causes of anemia, and possible increases in malaria and mortality risk resulting from overprescription of iron.…”
Section: Introductionmentioning
confidence: 99%